THE DIALECTICS OF RELIGIOUS PURIFICATION, TRADITION PRESERVATION, AND GLOBAL CHALLENGES IN ISLAMIC RELIGIOUS EDUCATION - Amiq, Bahrul; Soebahar, Abdul Halim; Mursalim; Amal, M. Khusna (AL-ADABIYAH: Jurnal Pendidikan Agama Islam, 2025)
This article examines the dialectics between religious purification, tradition preservation, and global challenges within the context of Islamic religious education in Indonesia. The study employs library research with a descriptive–critical method, reviewing classical and contemporary literature related to Islam Nusantara, globalization, modernization, radicalism, and religious education practices. The findings reveal that religious purification emphasizes returning religious practices to authoritative texts, whereas the preservation of local traditions highlights the integration of cultural values as a means of social harmonization and strengthening community identity. The tension between these two orientations influences the curriculum, learning strategies, and religious experiences at the local level. Globalization and modernization add further complexity by introducing transnational authorities and value homogenization, while also creating opportunities for cultural glocalization and the revitalization of local traditions. Religious radicalism emerges as an extreme response to social change, whereas cultural resistance functions as an adaptive mechanism for communities to maintain local wisdom. This study underscores the need for Islamic religious education to negotiate between doctrinal purity, local cultural contexts, and global demands in order to produce adaptive, contextual, and relevant educational practices. These findings contribute to a deeper understanding of the relationship between religion and culture, inclusive Islamic educational strategies, and the development of literature on Islam Nusantara in the global era.